Antigenotoxic, antiproliferative and antimetastatic properties of a combination of native medicinal plants from Argentina. (1st March 2021) - Carabajal, Monica Patricia Antonella; Piloto-Ferrer, Janet; Nicollela, Heloiza Diniz; Squarisi, Iara Silva; Prado Guissone, Ana Paula; Esperandim, Tábata Rodrigues; Tavares, Denise Crispim; Isla, María Inés; Zampini, Iris Catiana
Abstract: Ethnopharmacological relevance: Jarilla is the common name of an appreciated group of native plants from the semi-arid region in Argentina ( Larrea cuneifolia Cav., Larrea divaricata Cav. and Zuccagnia punctata Cav.) that have been historically consumed to heal respiratory, musculoskeletal and skin ailments, as well as recommended for weakness/tiredness, hypertension, diabetes and cancer treatment. It was previously reported that some biological properties could be improved when these plants are used jointly. Infusions of a defined mixture, composed by three Jarilla species, L. cuneifolia : L. divaricata : Z. punctata (0.5:0.25:0.25) (HM2) showed synergistic and additive effect on antioxidant activity even after passing through the gastro-duodenal tract. Aim of the study: The main purpose of this work was to evaluate antigenotoxic, antitumor, and anti-metastatic properties of the Jarilla species that grow in the Northwest of Argentina and a herbal combination of them. Material and methods: Infusions of Jarilla mixture (HM2), and of each single plant species were prepared. Phenolic profiles of infusions were analyzed by HPLC-ESI-MS/MS and two relevant chemical markers were quantified. The antigenotoxic activity was evaluated by using the Ames test and the Cytokinesis-Block Micronucleus (CBMN) assay against direct mutagens. Evaluations of both cytotoxicity and antiproliferative effects were conducted on tumor and non-tumor cell lines. Both in vivo tumoral growth and metastasis inhibition were evaluated by using a carcinoma model on Balb/c mice. Results: HM2 mix could suppress genetic and chromosome mutations induced by 4-nitro-o-phenylendiamine (4-NPD) and doxorubicin. Herbal mixture and single plant infusions showed cytotoxic effect against mammary, uterus, and brain tumoral cells without a selective action vs normal human cell line. HM2 mix was able to reduce mammary tumor mass on the Balb/c mice model and showed a significant reduction in the number of metastatic nodules in the lungs. Conclusions: Our results suggest that the combinations of three Jarilla species from northwest Argentina would be a promising alternative to treat or slow down the development of chronic diseases, such as cancer. Graphical abstract: Image 1 Highlights: A ternary herbal mixture, HM2, from "jarillas" was standardized by phenolic profile. Neither single plants nor HM2 induce DNA damage on Ames Test. HM2 shown antigenotoxic effect, while each individual plant did not show it. At low doses, HM2 protects DNA against mutagens on cell lines assays. HM2 demonstrated tumor growth inhibition and anti-metastatic effect in vivo.